Planning distribution primary feeders for smart-grid operation via network flow analysis (2015)
Planning the expansion of distribution systems (DS) is a nonlinear and combinatorial problem that combines technical and regulatory constraints. Commonly, the planning of DS is intended to achieve a radial topology to reduce its complexity. However, in a smart-grid context, distribution feeders are subject to reconfigurations to transfer load between feeders in failure events, or to compensate for voltage profile and power quality issues caused by distributed generation (DG). In this paper we propose a novel methodology for the planning of primary feeders, which considers the DS performance in both open and closedloop arrangements. To this end we introduce the concept of reach current, which we use to define and solve a minimum power-loss flow problem. We solve this problem for each type of conductor considered to find a set of primary-feeder candidates. Additionally, an efficiency evaluation is performed to select the best among the candidate primary feeders. Simulation results on a test system show how this method is able to capture open and closed-loop operations, explicitly considering DG in the DS expansion planning within a smart-grid scheme.